2018
DOI: 10.4103/sja.sja_409_17
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study on the impact of low-dose dexamethasone on perioperative blood glucose concentrations in diabetics and nondiabetics

Abstract: Background:Dexamethasone is a potent corticosteroid when administered alone or in combination alone has proven efficacious in preventing nausea and vomiting (PONV) perioperatively. However, the administration of even a single dose has been associated with hyperglycemia. This is the first study that evaluates the effect of two low-doses of dexamethasone (4 and 8 mg) on blood glucose concentrations among diabetics and nondiabetics in patients who have received spinal anesthesia.Materials and Methods:After obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Based on this survey there is concern regarding the use of perioperative single dose dexamethasone within the diabetic cohort of patients, particularly those with insulin dependent diabetes. Two recent randomised control trials [14,15] have reported a significant increase in blood glucose levels following dexamethasone administration in both diabetic and non-diabetic patients although there was no significant difference in the size of the effect between diabetics/non-diabetics in either study. A recent Cochrane review [16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this survey there is concern regarding the use of perioperative single dose dexamethasone within the diabetic cohort of patients, particularly those with insulin dependent diabetes. Two recent randomised control trials [14,15] have reported a significant increase in blood glucose levels following dexamethasone administration in both diabetic and non-diabetic patients although there was no significant difference in the size of the effect between diabetics/non-diabetics in either study. A recent Cochrane review [16].…”
Section: Discussionmentioning
confidence: 99%
“…The full versions of 41 articles were retrieved after screening and conducting a detailed selection process. Finally 16 articles (Nazar et al 2011;Tien et al 2016;Nazar et al 2009;Corcoran et al 2021a;Backes et al 2013;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Herbst et al 2020;Godshaw et al 2019;Allen et al 2020;Egan et al 2019;Harding et al 2021;O'Connell et al 2018;Corcoran et al 2021b) met the inclusion criteria and underwent data extraction. The details of the screening procedure are shown in Fig.…”
Section: Literature Search and Retrievalmentioning
confidence: 99%
“…The 16 included studies (Nazar et al 2011;Tien et al 2016;Nazar et al 2009;Corcoran et al 2021a;Backes et al 2013;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Herbst et al 2020;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Administration of dexamethasone raises blood glucose levels posing unique challenges in patients with diabetes. For diabetic patients, there is conflicting evidence regarding whether or not there is a dose dependent response in the elevation of blood glucose levels [16][17][18]. The anti-inflammatory nature of corticosteroids, through inhibition of prostaglandin synthesis, may also have detrimental side effects with high or repeated dosing.…”
Section: Introductionmentioning
confidence: 99%